Exercise for osteoporosis: A literature review of pathology and mechanism - Zhang, Lin; Zheng, Yi-Li; Wang, Rui; Wang, Xue-Qiang; Zhang, Hao (Frontiers in Immunology, 2022)
Osteoporosis (OP) is a disease that weakens bones and has a high morbidity rate worldwide, which is prevalent among the elderly, particularly, women of postmenopausal age. Dynamic balance between bone formation and resorption is necessary for normal bone metabolism. Many factors, including aging, estrogen deficiency, and prolonged immobilization, disrupt normal apoptosis, autophagy, and inflammation, leading to abnormal activation of osteoclasts, which gradually overwhelm bone formation by bone resorption. Moderate exercise as an effective non-drug treatment helps increase bone formation and helps relieve OP. The possible mechanisms are that exercise affects apoptosis and autophagy through the release of exercise-stimulated myohormone and the secretion of anti-inflammatory cytokines via mechanical force. In addition, exercise may also have an impact on the epigenetic processes involved in bone metabolism. Mechanical stimulation promotes bone marrow mesenchymal stem cells (BMSCs) to osteogenic differentiation by altering the expression of non-coding RNAs. Besides, by reducing DNA methylation, mechanical stimulus can also alter the epigenetic status of osteogenic genes and show associated increased expression. In this review, we reviewed the possible pathological mechanisms of OP and summarized the effects of exercise on bone metabolism, and the mechanisms by which exercise alleviates the progression of OP, in order to provide reference for the prevention and treatment of OP.